Differences in VO2 max readings between treadmill and cosmed K5 for elite boxers - Bushati, M.; Bushati, S.; Bendo, A.; Kosta, O. (International Journal of Disabilities Sports and Health Sciences, 2025)
Purpose of the study: The purpose of this study was to analyze the effectiveness of the accurate and best method for assessment of VO2 max in both treadmill and Cosmed K5 data. Method: The subjects of this study included 20 competitive male senior boxers mean 22.81 (SD = 3.59) years, height 178.83 (SD = 8.56) cm, body mass 78.28 (SD = 12.54) kg, and body mass index BMI 24.43 (SD = 3.45) kg/m2, with a range of 17.5 years and respective variances. Boxers have 5-10 years of competitive experience. Analyzing the data, descriptive statistical methods, descriptive statistical indicators, paired samples t-tests, independent samples t-tests analyses, and effect size calculations (Cohen`s d) were used, with a significance level of p < 0.05. Findings: The results showed that there was a statistically significant increase of VO2 max. from pre- to post-training measurement (p < 0.01), respectively, in both treadmill and Cosmed K5. The VO2 max values with the treadmill were higher compared to those of the Cosmed K5 method; the absolute change value of 13.4% with K5 measurements was greater compared with the absolute change of 8% for the treadmill. Conclusion: The main findings of this study are that improvements of VO2 max values with Treadmill in VO2 max are slightly greater than those reported with the Cosmed K5 method. The results of this study serve to change the concept that applying a special training program, such as HIIT, these exercises can improve performance levels of aerobic capacity and oxygen uptake.